PENDIDIKAN KARAKTER DALAM PERSPEKTIF FILOSOFIS - Hamid (Al'Adalah, 2015)
Since 2500 years ago, socrates said that the purpose of the fundamental of education is to make someone to be good and smart. In the history of Islam, about 1500 years ago Muhammad SAW, the last prophet in the teachings of Islam, also suggests that main mission in educating man is to seek develop the good character. Next, thousands of years after that, the main objective of education formulation remain at the same, namely the formation of good human personality. Character education is a system planting values of character to the schools that includes components knowledge, consciousness or volition, and action to values implementation, both with to respect of Allah SWT, yourself, others, environment, and nationality to be perfect human (insan kamil).